Prediction of optimum radio station place with ray tracing based models - Tabakcıoğlu, Mehmet Barış (Balıkesir Üniversitesi, 2020)
Deploying of a base station to correct place is vital to install high quality of service (QoS) and reliable terrestrial broadcasting systems. In order to make this process firstly coverage maps are generated for all possible base station places and then these coverage maps are compared among. Buildings and hills block the rays emanating from the base station to user. In these situations, electric field can be calculated by slope diffraction (S-UTD) and Uniform Theory of diffraction (UTD) models. In this study, optimum radio station place has been determined with S-UTD and UTD models and the results are compared for randomly distributed (10x10) 100 obstacles.

Servis kalitesi yüksek, güvenilir karasal yayıncılık sistemleri kurmak için baz istasyon yerinin doğru seçilmesi çok önemlidir. Bu işlem için her bir muhtemel baz istasyon yeri üzerinden kapsama alanları çıkarılmakta ve bu haritalar karşılaştırılmaktadır. Binalar ve tepeler baz istasyonundan çıkan ışınların kullanıcıya ulaşmasını engeller. Bu durumlarda elektrik alan Eğim kırınımı (EK) ve Uniform Kırınım teorisi (UKT) modelleriyle bulunabilir. Bu çalışmada EK ve UKT modelleri kullanılarak rasgele yüksekliklere sahip (10x10) 100 engel için en uygun radyo istasyonu yeri tespit edilmiş ve sonuçlar karşılaştırılmıştır.
Işın tabanlı modellerle en uygun radyo istasyon yeri kestirimi
215E360
Keywords: Engineering; Mühendislik